Correction: Extraversion personality, perceived health and activity participation among community-dwelling aging adults in Hong Kong - Lai, Daniel W. L.; Qin, Nan (PloS one, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0209154.].